CLINICAL CRITERIA FOR DIAGNOSING MENOPAUSE - Goulart, Danielle Magalhães Sá; Toledo, Rodolfo Ricardo; de Sousa, Gabriela Marinho Chagas; de Sousa, Nayara Sâmia Vaz Borges; dos Reis, Felipe Lessa; de Sousa, Hiago; Trindade, Elizandra Pereira (Seven Editora, 2026)
The diagnosis of menopause, a natural biological milestone defined retrospectively by the cessation of menstrual cycles for 12 months, remains predominantly clinical. However, identification is complex due to symptomatic variability, including Vasomotor Symptoms (VMS) and Genitourinary Syndrome of Menopause (GSM), and overlap with other health conditions. This study, characterized as a narrative literature review, sought to synthesize contemporary scientific evidence on clinical criteria for the diagnosis of menopause. The results reinforce that the diagnostic cornerstone is prolonged amenorrhea, but highlight Anti-Müllerian Hormone (AMH) as the most sensitive biomarker for predicting and identifying early stages of the transition, being a complementary resource, not an isolated criterion. Frequent clinical manifestations, such as VMS, contribute to the characterization, aided by the STRAW+10 classification system. This study highlights the diagnostic complexity in specific populations (such as cancer survivors) or in the presence of atypical complications (such as postmenopausal endometriosis), requiring a careful and integrated clinical approach. It concludes that accurate menopause diagnosis demands the integration of menstrual patterns and rigorous evaluation of systemic symptoms, aiming for comprehensive and individualized women's health care.